News jako funkcja - Kudra, Andrzej (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2010)
The aim of the author is to demonstrate that “news” is not a genre similar to notice, dispatch, signal etc., but rather a new information, which is unexpected, uncommon. It is the information and not the form which is the essence of news. News is a function not a genre.